KAJIAN KESESUAIAN LAHAN TANAMAN CENGKEH (Eugenia aromatica L.) BERDASARKAN ASPEK AGROKLIMAT DAN KELAYAKAN EKONOMI (Studi kasus Provinsi Sulawesi Selatan)CROP LAND SUITABILITY FOR CLOVE (Eugenia aromatica L.)... - Anisa Isnaeni; Yon Sugiarto (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2010)
Indonesian plantations are increasingly expanding and making progress so as to support the government programs in Indonesia Agricultural development is necessary, especially the plantation area of clove plantations which have many benefits and uses for the community.The aims of this study is to find out the suitability of the clove crop land in South Sulawesi province and the level of effectiveness in investing land. Methodology used is based on suitability area for agroclimate parameters and economical feasibility.The results of analysis shown that South Sulawesi Provinve are potential for extension based on the suitability of clove plants Agro-climate and the closure of its land in the amount of 26.743 km2.There are three land suitability classes, highly suitable areas or S1 (1.897 km2), moderately suitable areas or S2 (23.120 km) and marginally suitable areas or S3 (990 km2). In addition, the region still has the potential areas of land for plantation development is a form of forest land with an area of 8.694 km2.These three land suitabilitieshave feasibility of investment net profit in the S1 field with the present value of Rp 26.841.000/ha, 30,1% IRR, and BCR of 2,16.Net profit in the land S2 is Rp 16.864.000/ha, 24% IRR, and BCR of 1,73%, while net profit on the land S3 is Rp 2.723.000/ha.Areas of land which became the main development priorities with highprioritylandpresentinsixdistrictsnamelyWajo,Jeneponto,Sinjai,Bulukumba,Barru,andBoneIndonesian plantations are increasingly expanding and making progress so as to support the government programs in Indonesia Agricultural development is necessary, especially the plantation area of clove plantations which have many benefits and uses for the community.The aims of this study is to find out the suitability of the clove crop land in South Sulawesi province and the level of effectiveness in investing land. Methodology used is based on suitability area for agroclimate parameters and economical feasibility.The results of analysis shown that South Sulawesi Provinve are potential for extension based on the suitability of clove plants Agro-climate and the closure of its land in the amount of 26.743 km2.There are three land suitability classes, highly suitable areas or S1 (1.897 km2), moderately suitable areas or S2 (23.120 km) and marginally suitable areas or S3 (990 km2). In addition, the region still has the potential areas of land for plantation development is a form of forest land with an area of 8.694 km2.These three land suitabilitieshave feasibility of investment net profit in the S1 field with the present value of Rp 26.841.000/ha, 30,1% IRR, and BCR of 2,16.Net profit in the land S2 is Rp 16.864.000/ha, 24% IRR, and BCR of 1,73%, while net profit on the land S3 is Rp 2.723.000/ha.Areas of land which became the main development priorities with highprioritylandpresentinsixdistrictsnamelyWajo,Jeneponto,Sinjai,Bulukumba,Barru,andBone